АMINO ACID BALANCE PLASMA AND MONOCYTES IN PATIENTS WITH TUBERCULOSIS AS A FACTOR, REFLECTS THE SEVERITY OF DEVELOPMENT OF TUBERCULOSIS - S. N. Skorniakov; E. V. Sabadash; I. D. Medvinsky; B. I. Novikov; V. A. Pavlov (Медицинская иммунология)
The study included 90 patients with pulmonary tuberculosis who were divided into 3 groups, according to intensity and clinical form of the disease. Group 1 included 32 patients with infiltrative tuberculosis and two-segment pulmonary lesions; group 2, 31 patients with pulmonary tuberculoma, and group 3, 27 patients with fibrous/cavernous tuberculosis for less than two years after the process stabilization. Group 4 represented a control (comparison) group of 30 healthy volunteers. The analysis showed that amino acid balance of monocytes in pulmonary tuberculosis can be, in general, characterized as deficient for antioxidant resources. In case of tuberculous inflammation, the criteria of specific resistance comprise a necessary taurine pool to greater extent than glutathione oxidation in immunocompetent cells. The plasma/monocyte taurine ratios exhibit different values, depending on clinical form of pulmonary tuberculosis. Redistribution of plasma amino acids to the monocytes, or, vice versa, probable “washout” certain amino acids from the cells may be considered a factor that reflects severity of the infectious process.